Innovating, teaching & learning through flipped classroom workshop / E. Tavasuria Elangovan - Elangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
The objectives of the workshop were to give an exposure to the lecturers on the 21st century teaching skills in Sci-ence, prepare and produce skilled and competent lec-turers in the field of 21st century pedagogy, and train the lecturers of the faculty to apply the latest technology in teaching and learning process. Furthermore, the lecturers were also guided on how to prepare a lesson plan based on the new pedagogy. The talk given by Dr. Norliza has benefited the FSG lec-turers tremendously regarding the 21st century new ped-agogical trends in teaching and learning process. In the workshop, the FSG lecturers were exposed to a new in-structional strategy, 'Flipped Classroom' which reverses the traditional lecture-in-class format to blended learning by delivering instructional content through online and out-side of the classroom learning environment.